2018
DOI: 10.1142/s0217979218500261
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic, elastic and lattice dynamical properties of CdIn2Te4 under pressure from first principle

Abstract: The first-principle calculations have been performed to study the pressure-induced effects on the structural, electronic, elastic and lattice dynamical properties of defect chalcopyrite CdIn2Te4. The optimized structural parameters are well consistent with the available experimental and theoretical data. The evolutions of energy gaps, elastic constants, elastic moduli, phonon dispersion spectra, and Raman scattering spectra, as well as zone-center phonon frequencies with pressure have been investigated in deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Defect-chalcopyrites (DCs) are special type of semiconductors of A II B2 III C4 VI family, which have an ordered vacancy compounds (OCV) structure. They have potential applications in the areas of solar cells, optoelectronics, linear and nonlinear optical devices [1][2][3][4][5][6][7][8][9]. As a result, much emphasis has been placed on the experimental synthesis and structural characterization of these materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defect-chalcopyrites (DCs) are special type of semiconductors of A II B2 III C4 VI family, which have an ordered vacancy compounds (OCV) structure. They have potential applications in the areas of solar cells, optoelectronics, linear and nonlinear optical devices [1][2][3][4][5][6][7][8][9]. As a result, much emphasis has been placed on the experimental synthesis and structural characterization of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the Bridgman and chemical vapor transport (CVT) methods have been used to investigate their properties, which are observed by X-ray diffraction and Raman scattering [10][11][12][13][14][15][16][17]. Whereas theoretically, the density functional theory (DFT) has been used by different workers [2][3][4][5][18][19][20]. Recently, the authors have also used the first-principle calculations to investigate the different linear properties of LiGaS2, LiGaSe2, ZnGeN2 semiconductors [21,22], and functionalized graphene semiconductors [23].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have reported growing interest in this group of compounds due to their potential device applications. In the literature, there are several studies on material characteristics of CuInTe 2 , AgInTe 2 , CdIn 2 Te 4 , HgIn 2 Te 4 and also ZnIn 2 Te 4 [20][21][22][23][24][25][26]. However, this type of investigation would primarily require a rigorous study of Si-based heterojunction.…”
Section: Introductionmentioning
confidence: 99%